A simulation study of tritium removal from molten salt at high temperature with tritium permeation through metallic material. (1st June 2022) - Zeng, You-shi; Zhang, Qin; Deng, Ke; Chu, Xin-xin
Highlights: A simulation for tritium removal directly from molten salt with the metallic permeator. The key influencing factors are studied in this article. It is showing the way forward for removing tritium from molten salt with the permeator. Abstract: Tritium control was a challenge of the development of the Molten Salt Reactors. Researchers have proposed a method using the metallic permeator to remove tritium directly from molten salt, which was based on the property of tritium easily permeating through the metallic materials at high temperature. A shell and tube type of metallic permeator was simulated and analyzed for tritium removal efficiency and its influencing factors. Results showed the tritium removal efficiency of the permeator would be improved by increasing the proportion of tritium in T2 (or HT) form to total tritium in molten salt, the mass transfer coefficient of T2 (or HT) transferring from molten salt surface to metal surface, and the hydrogen permeability of the permeator. However, these effects were associated and the single factor might only work at certain conditions. And for now, the process of T2 (or HT) transferring from molten salt surface to metal surface is the rate-determining step in tritium removal process of the permeator, which indicated the limitation of tritium removal efficiency of the permeator was due to the low mass transfer coefficient rather than the low permeability of tritium permeating through the permeator metal. Thus, improving the mass transfer coefficient by the structure optimal design of the permeator is an available approach to get a high-efficiency of tritium removal.